IMPLEMENTASI KEBIJAKAN PERLINDUNGAN MELALUI MODEL PEMBINAAN TERHADAP ANAK JALANAN - Rahman, Nur; Rahman, Nur (Jurnal De Jure Muhammadiyah Cirebon, 2017)
The phenomenon of street children at Cirebon was a phenomenon that can not be underestimated, especially in the presence of various cases of exploitation are close to the lives of street children. In addition, the number of street children at Cirebon also increased at the end of 2014 and compared to the previous years. As a form of attention in handling the problem of street children, Cirebon has policies relating to issues of protection of street children, one of which is through the Regional Regulation No. 6 of 2009 on the Protection of Displaced Children and Children with Special Protection at Cirebon. The purpose of this study is to analyze the implementation of the policy on protection through coaching model for street children refers to the Regional Regulation No. 6 of 2009 on the protection of displaced children and children with special protection at Cirebon and analyzes about the efforts made by the Government of Cirebon and its barriers found in the coaching model provides protection against street children at Cirebon. The type used in this research is descriptive. Qualitative research data acquisition procedure, the data obtained from interviews, observations, and archival. The results of the study were considered to be relevant to the problem under study were analyzed qualitatively through data reduction according to the subject matter of the research and focused on the main issues to be answered in this study. The results showed that, under the regulations there are some programs have been done such as, (1) Step protection by using a coaching model of street children conducted at Cirebon that includes coaching prevention; ongoing formation; social rehabilitation efforts, (2) reducing the exploitation behavior, (3) and empowering of street children, (4) provide guidance on an ongoing basement, (5) to increase community participation in providing guidance to street children. Furthermore, in carrying out this regulation, clearly there are factors that influence both its support and its inhibitors in which the supporting factors consists of (1) the availability of regulation as the legal ground minimize the number of street children well, (2) Emergence of cooperation between local government and private companies, (3) availability of adequate resources to foster street children, (4) Availability of facilities and infrastructure that supports street children program development and (5) an adequate budget. While inhibiting factor consists of (1) modernization, industrialization, urbanization (2) poverty, (3) social conditions, (4) social change and (5) community erroneous interpretation of the Sunan Gunungjati message that reads, "Ingsun titip tajug lan fakir miskin", From all the facts that occurred so that the authors say that the application of this rule is not much be better nor can?t be optimalized as expected so far.